Keterampilan Berpikir Kritis dan Pemecahan Masalah Mahasiswa - Nurul Mulyaningsih; Masduki Asbari; Riska Sri Rahmawati (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to show that students can be sensitive to issues or problems that occur in society so that the character of a